Pengaruh Penambahan Tulangan Tekan Terhadap Momen Kapasitas Lentur dan Daktilitas Balok - Jaya Permana; M. Muhtaris; Eka Susanti; Yanisfa Yanisfa (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2019)
Double reinforcement beam design, increasing the compressive reinforcement can increase the flexural capacity moment and ductility of concrete beams. This helps planners to improve flexural capacity moment with minimal dimensions, that are still acceptable in terms of aesthetics. The purpose of this study is to know how much influence the increasing compressive reinforcement can increase the flexural capacity moment and ductility of concrete beams. Experimental research with beam specimens 20x20x60 cm, 2D16 tensile reinforcement, fc’ 25 mpa and fy 320 mpa. With a ratio of compressive reinforcement to tensile reinforcement of 0.14; 0.25 and 0.59. Flexural strength testing uses flexible loading with a roll-pined joint. The process of load reading is yield phase until ultimate phase. The results of the analysis show an uses of increasing compressive reinforcement can increase the moment of flexural capacity and ductility. The addition of compressive reinforcement reached 25% from tensile reinforcement, can increase the moment of bending capacity by 4.47%, but uses compressive reinforcement reached 50% of tensile reinforcement, only increasing the bending moment capacity of 1.43%. For ductility, uses compressive reinforcement reaches 25% from tensile reinforcement, can increase ductility by 19.73% and an increase of 26.17% by adding compressive reinforcement up to 50% of tensile reinforcement. From these results it appears that the more improvements added, the more the ductility increases and the less the moment the flexural capacity increases.